Concentric macro EMG role in electrodiagnostic evaluation of inflammatory myopathies - Eman ElZamarany; Ayat Allah Farouk; Lamia Afifi; Sandra Ahmed; Eman Ashraf; Eman Attia; Marwa Shalaby (European Journal of Translational Myology)
Background: Inflammatory myopathies (IM) encompass a diverse group of systemic autoimmune muscle disorders, not easy to diagnose. Concentric-macro EMG is supposed to reflect electrical activity of the entire motor unit. It could help in electrophysiological characterization of inflammatory myopathies and recognizing earlier myopathic changes.